Adolescent Alcohol-use and Economic Conditions: A Multilevel Analysis of Data from a Period with Big Economic Changes - Mikael Svensson; Curt Hagquist (Örebro University School of Business, 2009)
This paper examines how the unemployment rate is related to adolescent alcohol use during a time period characterized by big societal changes using repeated cross-sectional adolescent survey data from a Swedish region, collected in 1988, 1991, 1995, 1998, 2002 and 2005. Individual level alcohol use is connected to local level unemployment rate to estimate the relationship using multilevel modeling. The results show that the unemployment rate is negatively associated with adolescents alcohol use. When the unemployment rate increases, more adolescents, mainly girls, do not drink at all. Regular drinking (2/month or more) is, on the other hand, unrelated to the unemployment rate. This implies that we may se decreases in adolescent alcohol use in the now expected real economic crisis with increasing unemployment.
Keywords: E32; I12; 330; alcohol use; unemployment rate; multilevel methods; Sweden